Online dating in Asia: a systematic literature review - May, Sarah Poh Low; Bolong, Jusang; Waheed, Moniza; Wirza, Julia (Human Resource Management Academic Research Society, 2022)
The use of apps and online sites is widespread in Asia. With the usage of apps like TanTan, Bumble, Momo, Grindr, and many more others being on the rise. This review aims to collect study data, to understand the online dating environment in Asia. To accomplish the set objective, this review is carried out following guidelines outlined in the ROSES review protocol. To identify articles, a search was done on Scopus and Emerald databases using a combination of keywords. Google Scholar was used as an additional database. 19 items from the search met the requirements for inclusion. According to the findings of this literature research, there is a large number of persons participating in digital dating in Asia. Several individuals use dating apps or websites to meet love and sexual partners, mingle, enjoy themselves, and fulfil their curiosity. Some apps are even used as anti-stigma tools, meaning people should be allowed the freedom to date or love regardless of sexual orientation (heterosexual or homosexual), age, race, religion and many other factors. The use of apps has also been linked to depersonalization issues, where users are prone to presenting an idealised version of themselves and their circumstances, to improve their success in mate selection. According to this review, some of the attributes considered during mate selection are age, height, income status; with most online dating requirements being materialistic, physical build and attractiveness-oriented, prioritizing desire to have children, and education level. Though there are many benefits, especially when it has helped during the COVID-19 pandemic where people are mostly staying home, digital dating has also been associated with risky casual sex behaviours and the promotion of substance abuse among dating app users in Asia. Yet, this study will benefit and is important for scholars and online dating application (apps) companies to understand that not all western theories are applicable in Asian community as westerners are known to be individualistic in nature and habits whereas Asians are collectivist and have different needs when it comes to online dating.